Pengaruh Work-Life Balance dan Kesehatan Mental terhadap Kinerja Akademik Mahasiswa Part-Time di Universitas Muhammadiyah Kalimantan Timur (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of work-life balance and mental health on the academic performance of part-time students. The research was conducted at Universitas Muhammadiyah Kalimantan Timur. This study used a quantitative method and employed multiple linear regression analysis with a total sample of 100 respondents. Data were collected through the distribution of questionnaires using Google Forms. The results of this study indicate that work-life balance has a partial influence on the academic performance of part-time students, and mental health also has a partial influence on their academic performance. These findings suggest that the better the balance between work and personal life, and the more stable the mental health condition of the students, the higher their academic performance tends to be.